Structural and Physicochemical Properties of Glycerol-Plasticized Edible Films Made from Pea Protein-Based Emulsions Containing Increasing Concentrations of Candelilla Wax or Oleic Acid - Dariusz Kowalczyk; Waldemar Kazimierczak; Emil Zięba; Magdalena Lis; Monika Wawrzkiewicz (Molecules)
Hydrophobization could improve the moisture resistance of biopolymer-based materials, depending on the methods and materials used, providing benefits for packaging applications. The aim of this study was to compare the effect of increasing concentrations (0–2.0%) of candelilla wax (CW) and oleic acid (OA) on the structural and physicochemical properties, including water affinity, of glycerol-plasticized pea protein isolate (PPI) films. OA acidified the film-forming solution and increased its viscosity more effectively than CW. At the highest concentration, OA prevented cohesive film formation, indicating a weakening of protein self-interaction. OA caused less yellowing, matting, and a smaller reduction in UV/VIS light transmittance compared to CW. Both lipids caused a slight reduction in the films’ water content. Phase separation (creaming) of CW enhanced surface hydrophobicity, resulting in a greater reduction in water vapor permeability than OA (~37–63% vs. 2–18%). The addition of lipids did not reduce film solubility or water absorption, and OA even increased these parameters. Increasing lipid content decreased the mechanical strength and stretchability of the films by 28–37% and 18–43%, respectively. The control film exhibited low heat-sealing strength (0.069 N/mm), which improved by 42% and 52% with the addition of CW and OA at optimal levels.